Factores sociales que influyen en el incumplimiento de roles y funciones en las familias del asentamiento humano Chequén, distrito Chepén, Región La Libertad en el año 2017. - Alvarez Romero, Mónica Malú (2018)
The Thesis report developed is: FACTORES SOCIALES QUE INFLUYEN EN EL INCUMPLIMIENTO DE ROLES Y FUNCIONES EN LAS FAMILIAS DEL AA.HH. CHEQUEN, DISTRITO DE CHEPEN, REGION LA LIBERTAD EN EL AÑO 2017, which is the reason for the present investigation. The Inductive, Descriptive, and Statistical Methods were used, which were used to identify, describe and find the correlations between the social factors and their influence on the fulfillment of the roles and functions of the families. Bibliographic sources, observation, interviews and survey were used, together with appropriate instruments for the collection of information. The problem posed for the development of this research was: What are the social factors that influence the failure of the roles and functions of the families of AA.HH. Chequén, Distrito de Chepén, Región La Libertad in 2017 ?, for which the hypothesis was formulated that indicates that the social factors that directly influence the non-fulfillment of family roles and functions are socio-economic deficiencies, that cause conditions of proclivity to the problems, and the scarce participation, which generates a climate of dissatisfaction and demotivation among the members. In this way, the general objective of the research is to investigate and analyze the influence of social factors that affect the fulfillment of the roles and functions that occur in families. Chapter I deals with the general aspects of the Distrito de Chepén, which will allow us to have a general knowledge about the context in which the AA.HH is located. Chequén; Chapter II deals with the socioeconomic conditions of families; Chapter III deals with the internal participation of families; and Chapter IV, on motivation and satisfaction within the families of AA.HH. Chequén, del Distrito de Chepén.. I hope that this report is a contribution to the knowledge about the problematic reality that it covers, about the social factors and its influence in the non-fulfillment of the roles and functions of the family.